Ultrafast single breath-hold cone-beam CT lung cancer imaging with faster linac gantry rotation. (June 2019) - Arns, Anna; Wertz, Hansjoerg; Boda-Heggemann, Judit; Schneider, Frank; Blessing, Manuel; Abo-Madyan, Yasser; Steil, Volker; Wenz, Frederik; Fleckenstein, Jens
Highlights: CBCT imaging speed of 18 °/s considerably reduces acquisition times to 10–20 s. Ultrafast CBCT imaging would strongly impact breath-hold lung treatment strategies. Reduced imaging time for maintained registration accuracy on high-contrast areas. Could be clinically applicable on high-contrast lung and palliative cancer care. Paves the way for future combined imaging and treatment in one breath-hold phase. Abstract: Purpose: Lung tumors treated with hypo-fractionated deep-inspiration breath-hold stereotactic body radiotherapy benefit from fast imaging and treatment. Single breath-hold cone-beam-CT (CBCT) could reduce motion artifacts and improve treatment precision. Thus, gantry speed was accelerated to 18°/s, limiting acquisition time to 10–20 s. Image quality, dosimetry and registration accuracy were compared with standard-CBCT (3°/s). Methods and materials: For proof-of-concept, image quality was analyzed following customer acceptance tests, CT-dose index measured, and registration accuracy determined with an off-centered ball-bearing-phantom. A lung-tumor patient was simulated with differently shaped tumor-mimicking inlays in a thorax-phantom. Signal-to-noise-ratio, contrast-to-noise-ratio and geometry of the inlays quantified image quality. Dose was measured in representative positions. Registration accuracy was determined with inlays scanned in pre-defined positions. Manual, automatic (clinical software) and objective-automatic (in-house-developed) registration was performed on planning-CT, offsets between results and applied shifts were compared. Results: Image quality of ultrafast-CBCT was adequate for high-contrast areas, despite contrast-reduction of ∼80% due to undersampling. Dose-output was considerably reduced by 60–83% in presented setup; variations are due to gantry-braking characteristics. Registration accuracy was maintained better than 1 mm, mean displacement errors were 0.0 ± 0.2 mm with objective-automatic registration. Ultrafast-CBCT showed no significant registration differences to standard-CBCT. Conclusions: This study of first tests with faster gantry rotation of 18°/s showed promising results for ultrafast high-contrast lung tumor CBCT imaging within single breath-hold of 10–20 s. Such fast imaging times, in combination with fast treatment delivery, could pave the way for intra-fractional combined imaging and treatment within one breath-hold phase, and thus mitigate residual motion and increase treatment accuracy and patient comfort. Even generally speaking, faster gantry rotation could set a benchmark with immense clinical impact where time matters most: palliative patient care, general reduction in uncertainty, and increase in patient throughput especially important for emerging markets with high patient numbers.